FLOW SIMULATIONS OF PIPELINE WITH VARYING DIAMETERS - Daniel, Dylan Au (Universiti Teknologi PETRONAS, 2020)
In the oil and gas industry, pipelines are used to transport products such as crude oil and natural gas to be processed into different products for consumers. Offshore pipelines are divided into two categories which are piggable and unpiggable pipelines. Unpiggable pipelines are pipelines which lacks in pigging facilities and have difficult sections along its length which restricts in-line inspection tool movement throughout the pipeline. Since in-line inspection tools cannot be implemented in unpiggable pipelines to inspect and assess its integrity, different methods are needed to assess the pipeline. Therefore, in this research, the flow hydrodynamics in multiphase flow and its effects towards the different length ratio was studied in the difficult sections of unpiggable pipeline using ANSYS Fluent.